Unrestricted somatic stem cells: interaction with CD34+ cells in vitro and in vivo, expression of homing genes and exclusion of tumorigenic potential - Jeltsch, Kathrin; Radke, Teja Falk; Maier-Laufs, Stephanie; Giordano, Frank Anton; Allgayer, Heike; Wenz, Frederik; Zeller, W. Jens; Kögler, Gesine; Frühauf, Stefan; Maier, Patrick (Cytotherapy, 2011)
Background aims - Transplantation of allogeneic hematopoietic stem cells (HSC) within the framework of hematologic oncology or inherited diseases may be associated with complications such as engraftment failure and long-term pancytopenia. HSC engraftment can be improved, for example by co-transplantation with mesenchymal stem cells (MSC). Recently, a new multipotent MSC line from umbilical cord blood, unrestricted somatic stem cells (USSC), has been described. It was demonstrated that USSC significantly support proliferation of HSC in an in vitro feeder layer assay. - Methods - A NOD/SCID mouse model was used to assess the effect of USSC on co-transplanted CD34+ cells and look for the fate of transplanted USSC. The migration potential of USSC was studied in a Boyden chamber migration assay and in vivo. Quantitative real-time polymerase chain reaction (qRT-PCR) for CXCR4, CD44, LFA1, CD62L, VLA4, RAC2, VLA5A and RAC1 were performed. NMR1nu/nu mice were used for a tumorigenicity test. - Results - After 4 weeks, homing of human cells (CD45+) to the bone marrow of NOD/SCID mice was significantly increased in mice co-transplanted with CD34+ cells and USSC (median 30.9%, range 7-50%) compared with the CD34+ cell-only control group (median 5.9%, range 3-10%; P=0.004). Homing of USSC could not be shown in the bone marrow. A cell-cell contact was not required for the graft enhancing effect of USSC. An in vivo tumorigenicity assay showed no tumorigenic potential of USSC. - Conclusions - This pre-clinical study clearly shows that USSC have an enhancing effect on engraftment of human CD34+ cells. USSC are a safe graft adjunct.
Elektronische Reproduktion der Druckausgabe
Gesehen am 05.07.2022
Im Zusatz zum Titel ist das Pluszeichen hochgestellt